Cystic Fibrosis Foundation : balancing venture philanthropy with treatment - Kinkead, Gwen, 1951- (London : Yale School of Management, 2020)
In 2020, Dr. Michael Boyle, the new president and CEO of the Cystic Fibrosis Foundation of Bethesda, Maryland, was in a fortunate position. He commanded a larger endowment than the biggest national medical charities, including the American Red Cross, the American Heart Association and the American Cancer Society: $4.2 billion, eleven times budgeted 2020 expenses. The money was earned through partnering with industry partners to create new drugs to treat Cystic Fibrosis, which have changed the condition from being fatal to a manageable disease and earned the found 3.7 billion dollars in revenue. However, these drugs fall short of being a cure and Dr Boyle must now decide how to spend the endowment. Should he invest substantial resources into finding a cure or focus more on helping those who have cystic fibrosis at the moment?
Originally Published InKinkead, G. (2020). Cystic Fibrosis Foundation: Balancing Venture Philanthropy with Treatment. 20-032-15. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Endowment of research